Rumah jamur solusi peningkatan ekonomi masyarakat Desa Seko Lubuk Tigo Kecamatan Lirik Riau - Zulfarina Zulfarina; Evi Suryawati; Yustina Yustina; Riki Apriyandi Putra; Hendra Taufik; Rita Anugerah; Wasisto Utomo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The objective of this service is to increase the economy of community at Seko Lubuk Tigo village of Lirik sub-district, and to meet the needs of the mushroom market by making mushroom houses. The method of this program was conducted in the form of counseling, accompaniment, and the demonstration of making mushroom house by involving the students of Riau University who are in carrying out a Student Study Service (KKN). The respons of community were very positive, and have high spirit in applying the technology of making Mushroom House. The community were very enthusiastic to make mushroom house as a new job opportunity. The output of this program is to make the oyster mushroom production house and the pocket book for mushroom production. It is expected that by conducting this program, the community can disseminate the technology which is accepted to be applied to other communities.